Heterotrophic Extracellular Enzymatic Activities in the Atlantic Ocean Follow Patterns Across Spatial and Depth Regimes - Hoarfrost, Adrienne; Arnosti, Carol (Frontiers in Marine Science, 2017)
Heterotrophic microbial communities use extracellular enzymes to initialize degradation of high molecular weight organic matter in the ocean. The potential of microbial communities to access organic matter, and the resultant rates of hydrolysis, affect the efficiency of the biological pump as well as the rate and location of organic carbon cycling in surface and deep waters. In order to investigate spatial- and depth-related patterns in microbial enzymatic capacities in the ocean, we measured hydrolysis rates of six high-molecular-weight polysaccharides and two low-molecular-weight substrate proxies at sites spanning 38°S to 10°N in the Atlantic Ocean, and at six depths ranging from surface to bottom water. In surface to upper mesopelagic waters, the spectrum of substrates hydrolyzed followed distinct patterns, with hydrolytic assemblages more similar vertically within a single station than at similar depths across multiple stations. Additionally, the proportion of total hydrolysis occurring above the pycnocline, and the spectrum of substrates hydrolyzed in mesopelagic and deep waters, was positively related to the strength of stratification at a site, while other physichochemical parameters were generally poor predictors of the measured hydrolysis rates. Spatial as well as depth-driven constraints on heterotrophic hydrolytic capacities result in broad variations in potential carbon-degrading activity in the ocean. The spectrum of enzymatic capabilities and rates of hydrolysis in the ocean, and the proportion of organic carbon hydrolyzed above the permanent thermocline, may influence the efficiency of the biological pump and net carbon export across distinct latitudinal and depth regions.